Minimizing policy-biased appraisals of the evidence on cannabis and psychosis - Hall, Wayne (Frontiers in Psychiatry, 2023)
Appraisals of the evidence on the relationship between cannabis use and psychosis are often biased by appraisers' pre-existing views on whether adult cannabis use should or should not be legal. This viewpoint gives examples of such policy-biased appraisals and suggests strategies for avoiding them.